2020
DOI: 10.3389/fphar.2020.00020
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Abnormalities and the Role of Vascular Endothelial Growth Factor in the Epileptic Brain

Abstract: Epilepsy is a chronic neurological disorder generally defined to be caused by excessive neuronal activity. Thus, excessive neuronal activity is the main target of the currently used antiepileptic drugs (AEDs). However, as many as 30% of epileptic patients show drug resistance to currently available AEDs, which suggests that epilepsy should be attributed not only to neuronal cells but also to other brain cells, such as glial cells and vascular cells. Astrocytes, pericytes, and endothelial cells in particular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 62 publications
(81 reference statements)
1
25
0
Order By: Relevance
“…Furthermore, increased VEGF levels in the CSF of PD patients has been found to be significantly correlated with BBB dysfunction and neurodegeneration (Zou et al 2017). Similarly, it is also true that barrier leakage at BBB aggravates epileptic progression and vice versa (Ogaki et al 2020). During BBB dysfunction, increased VEGF upregulates the expression of matrix metalloproteinase (MMP) in endothelial cells, which activates the VEGF/VEGFR signaling causing excessive angiogenesis in the epileptic brain (Ogaki et al 2020).…”
Section: Brainmentioning
confidence: 99%
“…Furthermore, increased VEGF levels in the CSF of PD patients has been found to be significantly correlated with BBB dysfunction and neurodegeneration (Zou et al 2017). Similarly, it is also true that barrier leakage at BBB aggravates epileptic progression and vice versa (Ogaki et al 2020). During BBB dysfunction, increased VEGF upregulates the expression of matrix metalloproteinase (MMP) in endothelial cells, which activates the VEGF/VEGFR signaling causing excessive angiogenesis in the epileptic brain (Ogaki et al 2020).…”
Section: Brainmentioning
confidence: 99%
“…Recently, the use of lab and synchrotron radiation based micro-computed tomography (micro-CT) has been increasingly used in preclinical studies to assess quantitative parameters including lung volumes, air spaces or lesions and mean lung density 14 19 . These measurements have been performed in an attempt to reflect the structural and functional competence of the lung during disease progression and in response to therapy in numerous animal models of lung diseases, such as cancer, fibrosis, emphysema and transplantation 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Activation of VEGF has been suggested to regulate PI3K/AKT and MEK/ERK cascades. Furthermore, VEGF is known to be involved in the trophic and neuroprotective effects of growth factors via binding to its tyrosine kinase receptors, particularly of which VEGFR2 (Flk-1) is proposed to mediate most of the neuron-specific effects of VEGF via mediating PI3K/AKT and MEK/ERK signaling [ 10 , 11 , 12 , 13 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, growing evidence revealed that improving mitochondrial function with activation of PI3K/AKT and MEK/ERK pathways might tend to inhibit phosphorylation of c-Jun-NH2-terminal kinase (JNKs) and p38, the second and third major signaling cassettes in the MAPK pathway, which majorly respond to inflammatory and cellular stress to promote inflammation and cell death, in neuronal cells under many neurological conditions, both in vitro and in vivo studies [ 66 , 67 , 68 ]. Overall, MEK/ERK pathways have been reported to play a crucial role in protecting neuronal cells from death under hypoxia, global ischemia, epilepsy, status epilepticus, and Parkinson’s disease [ 33 , 63 , 68 , 69 ]. Therefore, following status epilepticus, endogenous activation of PGC-1α may regulate the VEGF/VEGFR2 (Flk-1) signaling pathway that triggers PI3K/AKT and MEK/ERK cascades and also promotes the cAMP-CREB signaling axis [ 45 , 69 ], which regulates the anti-apoptotic B-cell lymphoma-2 (Bcl-2) family, the expression of autophagy [ 63 ] and lysosomal genes, and further contributes to neuron survival mechanisms in hippocampal neuronal cells [ 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation